World vs. Method: Educational Standard Formulation Impacts Document Retrieval - Marshall,Byron; Reitsma,Reindert (Proceedings of the Joint Conference on Digital Libraries (JCDL'11),Ottawa, Canada., 2011)
Although initiatives are underway in the educational community to consolidate disparate collections of educational standards, little has been done to explore the impact of educational standard formulation on information retrieval. Recent research contrasts two categories of educational standards: ‘World’ (topical domain-related concepts) and ‘Method’ (investigative and epistemological principles). This paper explores the information retrieval implications of the World vs. Method distinction. We find that experts are more likely to agree about which educational resources align with a Method standard but that a typical automatic standard assignment tool is more likely to assign a World standard to an educational resource. Further, a text-based information retrieval system is more likely to be accurate in retrieving documents relevant to a World standard as compared to a Method standard. These findings have implications both for educational standard formulation (combining World and Method components in a standard may improve retrieval) and for digital library builders who want to help teachers identify useful, standards-aligned learning objects.
Keywords: Accounting; BIS